Nationwide molecular surveillance of three Plasmodium species harboured by symptomatic malaria patients living in Ghana - Amoah, L.E.; Asare, K.K.; Dickson, D.; Anang, S-F; Busayo, A.; Bredu, D.; Asumah, G.; Peprah, N.; Asamoah, A.; Abuaku, B.; Malm, K.L. (Parasites & Vectors, 2022)
Background: Clinical presentations of malaria in Ghana are primarily caused by infections containing microscopic densities of Plasmodium falciparum, with a minor contribution from Plasmodium malariae and Plasmodium ovale. However, infections containing submicroscopic parasite densities can result in clinical disease. In this study, we used PCR to determine the prevalence of three human malaria parasite species harboured by suspected malaria patients attending healthcare facilities across the country. Methods: Archived dried blood spots on filter paper that had been prepared from whole blood collected from 5260 patients with suspected malaria attending healthcare facilities across the country in 2018 were used as experimental material. Plasmodium species-specific PCR was performed on DNA extracted from the dried blood spots. Demo‑ graphic data and microscopy data for the subset of samples tested were available from the original study on these specimens. Results: The overall frequency of P. falciparum, P. malariae and P. ovale detected by PCR was 74.9, 1.4 and 0.9%, respectively. Of the suspected symptomatic P. falciparum malaria cases, 33.5% contained submicroscopic densities of parasites. For all regions, molecular diagnosis of P. falciparum, P. malariae and P. ovale was significantly higher than diagnosis using microscopy: up to 98.7% (75/76) of P. malariae and 97.8% (45/46) of P. ovale infections detected by PCR were missed by microscopy. Conclusion: Plasmodium malariae and P. ovale contributed to clinical malaria infections, with children aged between 5 and 15 years harbouring a higher frequency of P. falciparum and P. ovale, whilst P. malariae was more predominant in individuals aged between 10 and 20 years. More sensitive point-of-care tools are needed to detect the presence of low-density (submicroscopic) Plasmodium infections, which may be responsible for symptomatic infections.
Research Article
Keywords: Symptomatic Malaria; Plasmodium falciparum; Plasmodium malariae; Plasmodium ovale; Malaria prevalence; Ghana